2021
DOI: 10.1002/bit.27787
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metabolic modeling of multiple sulfate‐reducing prokaryotes reveals versatile energy conservation mechanisms

Abstract: Sulfate-reducing prokaryotes (SRPs) are crucial participants in the cycling of sulfur, carbon, and various metals in the natural environment and in engineered systems.Despite recent advances in genetics and molecular biology bringing a huge amount of information about the energy metabolism of SRPs, little effort has been made to link this important information with their biotechnological studies. This study aims to construct multiple metabolic models of SRPs that systematically compile genomic, genetic, bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…In both hydrogen-and formate-cycling model, electrons released in the periplasm are cycling back to the cytoplasm through transmembrane electron transport complexes, thus providing electrons for sulfate reduction and energy conservation in DvH (Keller and Wall, 2011;Tang et al, 2021). Among them, the quinone reductase complex (QrcDCBA) (Venceslau et al, 2010) and the transmembrane complex (TmcABCD) were identified with high confidence (Table 1) in these samples.…”
Section: Proteomic Analysismentioning
confidence: 98%
“…In both hydrogen-and formate-cycling model, electrons released in the periplasm are cycling back to the cytoplasm through transmembrane electron transport complexes, thus providing electrons for sulfate reduction and energy conservation in DvH (Keller and Wall, 2011;Tang et al, 2021). Among them, the quinone reductase complex (QrcDCBA) (Venceslau et al, 2010) and the transmembrane complex (TmcABCD) were identified with high confidence (Table 1) in these samples.…”
Section: Proteomic Analysismentioning
confidence: 98%
“…Lactate utilisation (Figure 1B) is carried out under microaerophilic conditions by Proteobacteria, including pathogens such as Campylobacter and Salmonella species, which fully oxidise lactate to carbon dioxide and water (Gillis et al, 2019). Desulfovibrio species, on the other hand, can convert lactate to acetate, together with the dissimilatory reduction of sulphate to sulphide (Marquet et al, 2009;Tang et al, 2021). Within the Firmicutes phylum, certain microbes are able to convert lactate to propionate or butyrate (Louis and Flint, 2017; Table 1).…”
Section: Biochemistry and Energetics Of Lactate Metabolismmentioning
confidence: 99%
“…Certain anaerobes have electron transport systems that work with alternative final electron acceptors. Thus, sulphate-reducing bacteria utilise sulphate to generate sulphide (Tang et al, 2021), and propionateproducing bacteria following the succinate pathway link the step from fumarate to succinate to electron transport (Seeliger et al, 2002).…”
Section: Energetics Of Lactate Metabolismmentioning
confidence: 99%
See 2 more Smart Citations